ANALISIS DAYA DUKUNG MONKEY FOREST UBUD SEBAGAI DAYA TARIK WISATA BERKELANJUTAN - Putri, Niken Prameswari; Rai, I Nyoman; Agung Suryawan, A.A.P (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
Monkey Forest Ubud is located in the Padang Tegal Village, Ubud District. The area of ????the tourism forest is about 12.5 ha. Tourism activities at Monkey Forest Ubud tend to be mass tourism activities. This study aims to measure the position of the effective carrying capacity of Monkey Forest Ubud based on biotic and abiotic variables, perceptions of tourism actors (tourists and management) towards tourism activities, condition of facilities and infrastructure and management of Monkey Forest Ubud, as well as alternative strategies for the realization of environmental sustainability and tourism. The method used to analyze the carrying capacity of the environment according to Cifuentes, drafting alternative sustainable management strategies for Monkey Forest Ubud with QSPM analysis. The results of the carrying capacity analysis show the ECC of 257 people/day. The average tourist visit in 2010-2019 reached 1,784 people/day, exceeding the ECC value indicates a threat to the biotic and abiotic factors that affect it. Alternative strategies resulting from the QSPM analysis for the realization of sustainable tourism with a score of 4.88 are alternative tourism in the form of educational tours in the Yadnya forest and event procurement in non-forest areas, the second strategy with a score of 4.86 is to maximize the digital marketing function, namely buying tickets online with providing daily visit quotas for tourist restrictions, the third strategy with a score of 4.66 is to increase ticket prices by 50% from normal tickets.The existence of the Ubud Monkey Forest has a positive impact on the social and economic aspects of the Padang Tegal Village community, but environmental sustainability needs to be considered, one of which is the restriction of tourist visits. Keywords: carrying capacity, sustainable tourism, Quantitative Strategy Planning Matrix